The decline and locational shift of automotive theft: A local level analysis. (March 2016) - Hodgkinson, Tarah; Andresen, Martin A.; Farrell, Graham
Abstract: Purpose: Investigate the changes in the spatial patterns of auto theft in Vancouver, British Columbia during a time of a significant crime drop. Methods: Geo-referenced auto theft data, 2003 and 2013, is analyzed considering crime concentrations at the street segment level, kernel density estimation, and a nonparametric spatial point pattern test that identifies the similarity in spatial point patterns. Results: Auto theft in Vancouver has dropped significantly, but does not appear to have a stable crime pattern. Specific and limited areas account for the crime drop in auto theft rather than occurring at all places. These places appear to be related to target suitability and, therefore, opportunity. Conclusions: The crime drop for auto theft in Vancouver has occurred in particular places. This provides support for the implementation of situational prevention efforts. Highlights: We analyze the spatial pattern of auto thefts in Vancouver, Canada. We use a nonparametric spatial point pattern test to identify changing patterns. We find significant changes in the spatial pattern of auto theft. The changes and decreases in auto theft are related to opportunity.